Development of a graphical user interface for 2D shape morphing - Paulina Konggidinata. (2009)
2D Morphing is a technique of gradually creating a smooth transformation from one shape to another which may be described by 2D curves or polygons. A 2D shape morphing application developed for this project is used as a testbed to transform a source to a target by computing intermediate values between the source and target points based on constraints specified by the user. The project aims to develop a framework for 2D morphing so that it can be efficiently incorporated with the existing 2D morphing algorithms. This framework will be used as a basis platform for experimenting and testing 2D morphing. In addition, this project also empowers user with the capability to conveniently and effectively control the whole morphing process. The focus of this project is to provide a more intuitive and user friendly GUI. In this project, 2D shape blending techniques which had been developed in Java were used as references to get a better understanding on how the morphing techniques perform. 2D shape morphing methods typically perform transformation in five stages from the source to destination shape. In the first step, for the two selected curves as the input to the program, we need to preprocess the raw data: normalize them into a common morphing window. In the second step, point simplification is performed to eliminate the duplicate vertex points of the source and destination polygons.